2015
DOI: 10.1182/blood-2014-12-603381
|View full text |Cite
|
Sign up to set email alerts
|

“Cup-like” blasts in acute myeloid leukemia with FLT3 and NPM1 mutations

Abstract: A 61-year-old man presented with left-side neck pain and swelling, dizziness, night sweats, and significant weight loss. His laboratory investigations showed pancytopenia with hemoglobin of 8.6 g/dL, leukocyte count of 600 per mL, and platelet count of 15 000 per mL. Bone marrow aspiration and biopsy revealed 90% blasts (panel A) with a peculiar "cup-shaped" nuclear morphology (panel B). Molecular diagnostics revealed the presence of cooccurring mutations of the nucleophosmin (NPM1) and Fms-like tyrosine kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…16 It is worth mentioning that the folded or indented nuclei observed in cutaneous tissue sections of leukemia cutis may represent the equivalent "cup-like" structures previously described in bone marrow specimens. 4 Table 1 provides a comprehensive summary of the clinical, morphological, immunophenotypic, cytogenetic, and molecular characteristics observed in previously reported cases of myeloid leukemia cutis with FLT3 and NPM1 mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 It is worth mentioning that the folded or indented nuclei observed in cutaneous tissue sections of leukemia cutis may represent the equivalent "cup-like" structures previously described in bone marrow specimens. 4 Table 1 provides a comprehensive summary of the clinical, morphological, immunophenotypic, cytogenetic, and molecular characteristics observed in previously reported cases of myeloid leukemia cutis with FLT3 and NPM1 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports of acute myeloid leukemia (AML) have revealed a strong association between the cup‐like nuclear morphology observed in bone marrow specimens and concurrent mutations of NPM1 and FLT3‐ITD or TKD 4–9 . In cutaneous tissue sections of leukemia cutis, folded or indented nuclei may represent the “cup‐like” counterpart previously described in bone marrow specimens.…”
Section: Introductionmentioning
confidence: 90%
“…However, methods to effectively treat the AML subtype with cup-like blasts in patients with mutations of both FLT3 and NPM1 or one of them remain unknown. Two previous studies suggested that cytarabine-based intensive chemotherapy might be effective in such patients [ 1 , 5 ]. Moreover, there are few therapeutic options in elderly patients due to their age, performance status and complications, which make them inappropriate for intensive chemotherapy and stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) is a molecularly and cytogenetically heterogeneous hematological malignancy. Previous studies have indicated a potential AML subtype characterized by a distinct cup-like blast phenotype with mutations of both FLT3 and NPM1 or one of them [1–5]. However, the clinical features, treatment and prognosis of this subtype remain to be depicted.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic subtype discrimination of AML derived blood smears is an ideal use case for explainable AI for two reasons: First, morpho-genetic correlations between the appearance of atypical cells and the PML::RARA fusion are established for APL and allow validation of the model. For other subtypes, morpho-genetic correlations are discussed, as in the case of a NPM1 mutation that is assumed to correlate with the appearance of blasts with a cup-like nuclear shape [18]. Second, the AML genetic subtype is included in the patient information, providing annotated training data without any label noise.…”
Section: Introductionmentioning
confidence: 99%